(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article describes the cooperative form of finance, what it is, how it works, as well as the activities of the cooperative. n this article, the theoretical foundations of corporate finance, interrelated sciences in researching the field, the history of its development, the opinions of foreign and domestic scientists on corporate finance, the relevance of introducing corporate finance as a science, the functions, goals and tasks of this science are reflected.